Teucrium polium L: An updated review of phytochemicals and biological activities - Seifollah Bahramikia; Parvaneh Hemmati Hassan Gavyar; Razieh Yazdanparast (Mashhad University of Medical Sciences, 2022)
Objective: Medicinal plants and their components are potential novel sources for developing drugs against various diseases. Teucrium polium L. (syn Teucrium capitatum L. or felty germander) from the Lamiaceae family, is widely distributed in the dry and stony places of the hills and deserts of almost all Mediterranean countries, southwestern Asia, Europe, and North Africa. Based on traditional Iranian medicine (TIM), T. polium is used for treating many diseases, including abdominal pain, indigestion, and type 2 diabetes.Materials and Methods: In our previous review article published in 2012 and based on 100 articles published from 1970 to 2010, the main compounds purified from T. polium were terpenes, terpenoids, and flavonoids with antioxidant, anticancer, anti-inflammatory, hypoglycemic, hepatoprotective, hypolipidemic, antibacterial, and antifungal activities.Results: In this article, the phytochemistry and pharmacological activities of the plant reported from 2011 to 2020 have been evaluated. Therefore, a search was done in the databases PubMed, Science Direct and Google Scholar, Scopus, and Web of Science with the terms "T. polium," "T. capitatum." and felty germander', which included about 100 articles published since 2011 about T. polium pharmacological activities and isolated compounds. Most studies of this review focused on the antioxidant and antidiabetic effects of the plantConclusion:. Considering the position of T. polium in folk medicine, mainly as an antidiabetic agent, purification, structural and biological characterization of the active components appears essential for effective use of the plant.